THE EFFECT OF KNOWLEDGE, COMMITMENT, DISCIPLINE AND WORKLOAD ON SERVICE PERFORMANCE WITH STRESS AND BURNOUT AS MEDIATION AND ACHIEVEMENT MOTIVATION AS MODERATION OF MEDICAL PRACTITIONERS IN GROBOGAN AND KUDUS REGENCIES, CENTRAL JAVA - Setyawan, Aris; Andjarwati, Tri; Nugroho, Riyadi (LPPM of NAROTAMA UNIVERSITY, 2023)
Improving and developing the quality of services carried out by the human resources in the hospital is the key to achieving the goals desired by the hospital as a health service provider. The purpose of this study was to determine the effect of knowledge, commitment, discipline and workload on service performance with stress and burnout as mediation and achievement motivation as moderation of medical practitioners in Grobogan and Kudus Regencies, Central Java. This research was quantitative research used 133 respondents from type B Hospital medical staff in Grobogan and Kudus Regencies, Central Java. Data analysis using SMART PLS. Based on the results of the analysis, it shows that for medical staff at Hospitals in Kudus and Grobogan Regencies, Central Java, knowledge has no significant effect on stress levels or performance, but has a significant effect on burnout. Commitment has no significant effect on stress or performance but has a significant effect on Burnout. Discipline has no significant effect on stress or burnout but has a significant effect on service performance. Workload has no significant effect on stress or burnout, but has a significant effect on service performance. Burnout has no significant effect on service performance. Achievement motivation is not able to significantly moderate the effect of stress on service performance and is unable to significantly moderate the effect of burnout on service performance in medical personnel in Hospitals in Kudus and Grobogan Regencies. The suggestions that need to be considered for future researchers can be applied to research objects that are not services, and future researchers are expected to use the same research model but use a different theoretical perspective.